Development banks make greener cities - Jiajun Xu; Xinyue Wu (10th World Urban Forum, 2020)
The world is facing the dual challenge of closing a vast urban infrastructure financing gap and making urban infrastructure more climate resilient. As estimated by the OECD, USD 95 trillion will be required to develop transport, energy, water, and telecoms from 2016 to 2030 in developing countries. With the temperature rise, the extreme weather will have direct physical harm on infrastructure as the aging infrastructures would be vulnerable to storm surges and sea level rise. In order to keep global temperature rise this century well below 2 degrees Celsius above pre-industrial levels, an additional 10% of investment will be needed to develop climate resilient infrastructure, adding to the USD 6.9 trillion needed per year by 2030.